Functional Neural Alterations in Pathological Internet Use: A Meta-Analysis of Neuroimaging Studies - Peng, Wei; Hao, Qinghong; Gao, Heng; Wang, Yang; Wang, Jun; Tu, Yang; Yu, Siyi; Li, Hui; Zhu, Tianmin (Frontiers in Neurology, 2022)
Previous studies have identified altered brain changes in patients with pathological Internet use (PIU). However, the findings were inconsistent in studies using different neuroimaging analyses. This meta-analytic study aimed to identify a common pattern of altered brain activity from different studies. Whole-brain functional Magnetic Resonance Imaging studies published before July 1, 2021, were searched in multiple databases (PubMed, EMBASE, MEDLINE, Web of Science). A voxel-based Signed Differential Mapping (SDM) method was used to clarify brain regions which showed anomalous activity in PIU patients compared healthy controls (HCs). Ten eligible publications consisting of 306 PIU patients and 314 HCs were included in the SDM meta-analysis. Compared with HCs, PIU patients showed increased spontaneous neural functional activity in the left temporal pole of the superior temporal cortex, left amygdala, bilateral median cingulate cortex, and right insula. Meanwhile, decreased spontaneous neural activity was identified in the left dorsolateral superior frontal gyrus and right middle frontal gyrus in PIU patients. These abnormal brain regions are associated with cognitive executive control and emotional regulation. The consistent changes under different functional brain imaging indicators found in our study may provide important targets for the future diagnosis and intervention of PIU.